Home Based Recreational Indoor Leisure Perception Of Female Viewers On My Trip My Advanture Television Show - Gustiarini, Anastasia; Avenzora, Ricky; Teguh, Frans (Media Konservasi, 2018)
Implementation of ecotourism concept for sustainable tourism in Indonesia until these day unfinished task. Insight for this concept must becontinuously and never end. Television is a mass media that very influent and play a role in promoting the principles of ecotourism. One of thetelevision programs that present content the various natural destinations tourism of Indonesia is My Trip My Advanture. This research will beanalyzed the motivation and perception of ecotourism of female audience for the natural destinations tourism based on program. Women especiallyfemale students are selected as respondents because has a good bargaining position and very strategic role model in family and society. The purposeof this study analyzed the motivation and perception of ecotourism of respondents and analyzed the relationship between the characteristicsrespondents to perception, motivation, and preference. The results showed that respondents understanding the meaning of ecotourism principle.Motivation and perception of impressions are scores of six from one to seven scale ranges program. That shows MTMA program has entered thepositive space. This supports the documentary program participating respondents do acts the responsible traveling for environmental, social andcultural conservation. The concept of ecotourism can also be accepted by all walks of life from diverse backgrounds reinforced by the analysis thatdifferent levels of characteristics do not affect the level of motivation, perception, and preferences.Keywords: ecotourism, female, My Trip My Advanture, television show